RELATIONSHIP BETWEEN POST BOWEL RESECTION ILEO-ILEAL INTUSSUSCEPTION: SYSTEMATIC REVIEW - Almalik Saputra, Yusuf; Poerwosusanta, Hery (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Intussusception is when the proximal segment of the intestine (intussusceptum) enters the distal segment (intussuscipiens) and when the opposite direction is known as retrograde intussusception. The aim: This study aims to explain the incidence, mechanism, diagnostic tool, and treatment of ileo-ileal intussusception after intestinal resection. Methods: This study can show that it meets all requirements by comparing itself to the standards the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Publications between 2013 and 2023 are considered. We excluded cut reviews and finished works. Result: This study lists five eligible studies. Conclusion: Surgical exploration is necessary to verify the diagnosis and exclude an underlying malignancy. However, there is no universal consensus regarding the indication for intraoperative reduction and the extent of bowel resection.